Penggunaan bahasa dan pemaparan gender dalam iklan majalah / Hadawiah Junaidi - Hadawiah, Junaidi (2012)
This study investigates the relationship between language and the gender component seen in magazine commercial advertisements. The focus of this study is on the use of written language as well as symbolic representations in magazine advertisement and their effects on the gender concept. The researcher adopted the concept proposed by Coates as the main framework in this study. According to Coates, masculinity and feminism can be reflected through language such as using specific set of words or phrases in demonstrating the gender in context. The commercial advertisements used in this study are categorized according gender of audience i.e males, females and neutral audiences (neutral i.e. for both genders). A questionnaire survey was done to substantiate the findings of this study. The questionnaire, which encompasses 21 items including male and female identity stereotype, was distributed to 100 respondents. The study showed that there is a difference in the use of language to characterize male and female identities.